2022
DOI: 10.1002/clc.23900
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome prediction for chronic thromboembolic pulmonary hypertension after pulmonary endarterectomy

Abstract: Background: The definitive treatment for chronic thromboembolic pulmonary hypertension (CTEPH) is pulmonary endarterectomy (PEA), which has good longterm outcomes. However, after surgery, a quarter of the patients still have residual pulmonary hypertension (RPH). In pulmonary hemodynamics, there are no unified criteria for RPH, even though the level may affect long-term survival.Methods: Between March 1997 and December 2021, 253 CTEPH patients were treated at our center with PEA. Patients were evaluated retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to reports from the University of California-San Diego Medical Center where the PEA technique was pioneered and developed, perioperative mortality decreases from 20% in the early stages to 2%, with 5- and 10 year survival rates of 82% and 75%, respectively, which were significantly improved compared with those who did not receive PEA [ 8 , 11 ]. Based on the most recent similar results from our center, which have become better over time, the perioperative death rate was 1.2% (2/171) in 2015, with a 10-year survival rate of 83.9% [ 10 ]. Similar to the prior CTEPH group, the majority of the patients in the current cohort did not have postoperative complications, including reperfusion pulmonary edema, pulmonary bleeding, delirium, or lung infection, regardless of whether an additional patch expansion of PA was performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to reports from the University of California-San Diego Medical Center where the PEA technique was pioneered and developed, perioperative mortality decreases from 20% in the early stages to 2%, with 5- and 10 year survival rates of 82% and 75%, respectively, which were significantly improved compared with those who did not receive PEA [ 8 , 11 ]. Based on the most recent similar results from our center, which have become better over time, the perioperative death rate was 1.2% (2/171) in 2015, with a 10-year survival rate of 83.9% [ 10 ]. Similar to the prior CTEPH group, the majority of the patients in the current cohort did not have postoperative complications, including reperfusion pulmonary edema, pulmonary bleeding, delirium, or lung infection, regardless of whether an additional patch expansion of PA was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the prior CTEPH group, the majority of the patients in the current cohort did not have postoperative complications, including reperfusion pulmonary edema, pulmonary bleeding, delirium, or lung infection, regardless of whether an additional patch expansion of PA was performed. These advancements might be attributed to the accumulated surgical expertise gained during the learning curve, bloodless vision with deep hypothermic circulatory arrest, enhanced perfusion strategy, and integrated management in the cardiac critical care unit [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A patient is deemed operable when adequate surgically accessible thromboembolic material is present, and a proportionate PVR indicates the absence of extensive distal disease. Notably, highly specialized centers have shown optimal success rates [ 3 ], and our institution recorded an overall survival rate of 91.2% and 83.9% at 5 and 10 years, respectively, for patients with CTEPH who underwent PEA [ 29 ]. Our study revealed no patients that died during hospitalization after PEA.…”
Section: Discussionmentioning
confidence: 99%